Preparation of chemically modified sago bark for oil sorption - Ranthi Rasthulini, Ahmad (UNIMAS, 2013)
Natural fibers have proved to be an excellent to clean up oil spill. The main disadvantage of the natural fibers to be used as clean up oil spill is their hydrophilic nature. Empty fruit bunch (EFB) and sago bark (SB) have been used as a raw material of this study because of its abundance, accessibility and suitability. EFB and SB were modified with esterification by steric acid in the presence of catalyst. Esterifications of fibers were done to reduce the hydrophilicity and thereby increasing the sorption characteristics. The SB and esterified sago bark (ESB) have been subjected to FTIR, SEM, density test, buoyancy test and hydrophobicity test to characterize the chemical and physical constituents. A detailed investigation on the oil sorption characteristics of SB and (ESB) has been carried out. Sorption test were conducted in dry system, wet static system and wet dynamic system. ESB has shown higher sorption capacity than SB. Hydrophilicity of the fibers decreased upon modification, which decrease water uptake and increase oil uptake.